Contract’s Meaning and the Histories of Classical Contract Law - Rosenberg, Anat (McGill Law Journal / Revue de droit de McGill, 2013)
This paper argues that histories of nineteenth-century contract have been implicated in the creation of a questionable historical artifact: the story of a single meaning of contract at the decisive era for modern contract law’s development, a story intimately tied with atomistic individualism.The paper traces how the consensus has been built and kept beyond debate despite significant controversies engaging rival historical schools of nineteenth-century contract law. It does so by critically synthesizing multiple accounts of contract law, produced from the nineteenth century to our own days. It opens, however, with a brief literary excursion in order to show that there is good reason to view the consensus as unwarranted. An individualist but relational version of contract was dominant in Victorian literary realism, one of the central cultural sites of the “Age of Contract”, problematizing the story of a single meaning of contract.The consensus created by contract histories bears implications for present thought as it negotiates visions of contract, and as it explores law’s constitutive effects on social consciousness. This paper lays the consensus open so that we can let go of it.